A Point‐of‐Care Raman Spectroscopy–Based Device for the Diagnosis of Gout and Pseudogout: Comparison With the Clinical Standard Microscopy. Issue 7 (July 2016) - Li, Bolan; Singer, Nora G.; Yeni, Yener N.; Haggins, Donard G.; Barnboym, Emma; Oravec, Daniel; Lewis, Steven; Akkus, Ozan
Abstract : Objective: To demonstrate the usefulness of a novel medical device based on Raman spectroscopy for the rapid point‐of‐care diagnosis of gout and pseudogout. Methods: A shoebox‐sized point‐of‐care Raman spectroscopy (POCRS) device was developed for use in the diagnosis of gout and pseudogout. The device included a disposable syringe microfiltration kit to collect arthropathic crystals from synovial fluid and a customized automated Raman spectroscopy system to chemically identify crystal species. Diagnosis according to the findings of POCRS was compared with the clinical standard diagnosis based on compensated polarized light microscopy (CPLM) of synovial fluid aspirates collected from symptomatic patients (n = 174). Kappa coefficients were used to measure the agreement between POCRS and CPLM findings. Results: Overall, POCRS and CPLM results were consistent in 89.7% of samples (156 of 174). For the diagnosis of gout, the kappa coefficient for POCRS and CPLM was 0.84 (95% confidence interval [95% CI] 0.75–0.94). For the diagnosis of pseudogout, the kappa coefficient for POCRS and CPLM was 0.61 (95% CI 0.42–0.81). Conclusion: Kappa coefficients indicated that there was excellent agreement between POCRS and CPLM for the diagnosis of gout, with good agreement for the diagnosis of pseudogout. The POCRS device holds the potential to standardize and expedite the time to clinical diagnosis of gout and pseudogout, especially in settings where certified operators trained for CPLM analysis are not available.